How does in-store and online shopping experiences influence repurchase intentions in Shandong, China? Roles of perceived value, brand trust, and customer satisfaction - Shuang Zhou; Norlaile Salleh Hudin (PLoS ONE, 2025)
For China’s omni-channel retailers, retaining customers is of utmost importance. This study identifies the key factors influencing customers repurchase intentions in retail stores. Through omni-channel integration, we propose a framework that explains how social media, store atmosphere, merchandise quality, service quality, and price perception impact repurchase intentions through functional, utilitarian, and hedonic value processing systems. The study utilized an online questionnaire targeting 305 respondents, primarily Chinese consumers, considering age, gender, and income levels to enhance methodological transparency. Data validation encompassed factor analysis, confirmatory factor analysis, and structural equation modeling. The results indicate that factors such as social media, store atmosphere, merchandise quality, service quality, and price perception significantly influence perceived value (serving as mediator variables). These perceived values play a crucial role in enhancing customer satisfaction and brand trust. Furthermore, customer satisfaction and brand trust increase repurchase intentions. The findings of this study offer valuable insights for optimizing customer experience in highly competitive markets like China, enhancing loyalty and repurchase intentions, and promoting the success of omni-channel retail strategies.